Effect of synchronicity of amino acid supply on the synthesis of protein in C2C12 myotubes cultured in vitro - Zhang, Qiyu; Mi, Mengmeng; E, Tianjiao; Fu, Xin; Bao, Nan; Pan, Li; Zhao, Yuan; Qin, Guixin (Frontiers in Veterinary Science, 2024)
Previous studies inferred that the synthesis rate/efficiency of protein in body tissue is probably affected by synchronicity of different amino acid (AA) supply in its metabolic pool. In order to further observe the influence of synchronicity of AA supply on the synthesis of protein in cell level, a cell culture experiment in vitro was conducted with C2C12 myotubes. C2C12 myotubes were cultured for 24 h, meanwhile the culture medium was replaced for each 8 h. Those myotubes were subjected to 3 treatments (1 for controlled and 2 for tested), control myotubes were cultured with same normal complete medium within the whole 24 h, and the 2 tested myotubes were cultured with asynchronous amino acid supply medium in which the levels of different AAs (Lysine, threonine, methionine, leucine, valine and glutamic acid) either increased and then decreased or decreased and then increased, at different replaced medium time point (at 0, 8, and 16 h). However, during the whole experiment period all the 3 treated myotubes received same amount of each AA. The sample of the myotubes were used for myotube morphology, protein, AA, and proteomic analysis. The results showed that asynchronous AA nutrition affect the synthesis and degradation of myotube proteins, and the AAAS in the medium increase, thus decreasing the synthesis rate of myotube proteins (p < 0.05) and decreasing the diameter of myotubes (p < 0.05). The process of reduced protein synthesis affects the PI3K-AKT and FoxO signaling pathway by downregulating the levels of IRS1 and EGFR, and the degradation amplitude is greater than the synthesis amplitude. Therefore, this study further revealed the effect of the asynchronous supply of amino acids on myotube protein synthesis and the underlying mechanism and provided a theoretical reference for the precision of nutrition to animals.